PS-096 METHADONE and LEVOMETHADONE: risks and costs analyses. (25th February 2017) - Pittet, N; De Giorgi Salamun, I; Simon, O; Hachaichi, M; Bergeron, E; Allaz, M; Wildhaber, A; Besson, J; Sadeghipour, F
Abstract : Background: Methadone oral solution 10 mg/mL is the gold standard in opioid agonist treatment (OAT). With the recent marketing authorisation of the levomethadone solution 5 mg/mL, cardiac toxicity has decreased but the risks of errors and confusion in prescriptions, preparation and administration seems to be significant and the costs will probably be high. Purpose: To analyse the risks of different dosage forms and product formulations from prescription to administration of methadone and levomethadone in the Ambulatory Addiction Treatment Centre (AATC) and general psychiatry. To assess the associated costs for the entire hospital. Material and methods: A multidisciplinary team identified and listed the failure modes (FM) and prioritised these based on their criticality indices using the failure modes, effects and criticality analysis. Improvement measures (IM) were proposed. An economic calculation compared the annual costs between methadone and levomethadone. Results: 61 FM were identified and organised in an Ishikawa diagram. Among the 25 most critical FM, 10 concerned the preparation step and 7 the prescription. 3 involved confusions or errors between methadone and levomethadone. 30 IM have been proposed including the following: An information letter about changes in treatments with OAT. A conversion table (mg/volume). Basic 'bedscanning' based on coloured stickers (prescription sheet and levomethadone bottle in orange; slow release oral morphine (SROM) in yellow); once the prescriber wants to change from methadone to levomethadone and/or SROM, depending on clinical risks of heart rhythm disorders induced by prolongation of the QTc interval. A checklist of preparation and administration steps. A clinical algorithm defining the use of levomethadone in the hospital, choosing between methadone and SROM, balancing costs and clinical risks. The purchase of a balance allowing the double checking of prepared doses (AATC). A systematic switch from methadone to levomethadone will generate an additional annual cost of €60 000 for the hospital. Conclusion: This study allowed the identification and quantification of the main risks related to methadone and levomethadone in our hospital. IM have been proposed taking into account the clinical and pharmacoeconomic aspects. A cost–benefit analysis would be a better assessment of the impact of levomethadone on morbidity/mortality and the costs involved. No conflict of interest